Unlikely partners : Chinese reformers, Western economists, and the making of global China - Gewirtz, Julian, 1989- (Harvard University Press, 2017)
How did China emerge from isolation and poverty under Mao Zedong to become the economic powerhouse shaping the 21st century? Soon after Mao died in 1976, China's leaders invited many of the leading foreign economists to come to China and sought their input on economic policy. This book demonstrates the constantly negotiated receptivity of Chinese policymakers who reached out to foreign economists and interpreted their ideas as they sought to incorporate market elements into their country's socialist economy. Working together, interacting in complex dynamics of influence and adaptation, they changed China.--